2003
DOI: 10.1521/scpq.18.3.253.22578
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Recess on the Classroom Behavior of Children With and Without Attention-Deficit Hyperactivity Disorder.

Abstract: The primary purpose of this study was to evaluate the effects of a traditional recess on the subsequent classroom behavior of children with a diagnosis of Attention-Deficit Hyperactivity Disorder (ADHD). In addition, the time of recess was matched to the behavior of the individual children diagnosed with ADHD based on prior assessment of their classroom behavior as a function of time of confinement in the classroom. All results were evaluated using single-case designs. Results showed that levels of inappropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 9 publications
1
29
0
1
Order By: Relevance
“…Attention to classroom tasks has been used in many studies of proximal effects of recess on cognitive performance (e.g., Jarrett et al, 1998;Ridgway et al, 2003). Attention is a direct and relatively easy-tomeasure index of children's motivation for, and engagement in, their school work (e.g., Toppino et al, 1991).…”
Section: The Role Of Recess In Cognitive Performance: Proximal Measuresmentioning
confidence: 99%
“…Attention to classroom tasks has been used in many studies of proximal effects of recess on cognitive performance (e.g., Jarrett et al, 1998;Ridgway et al, 2003). Attention is a direct and relatively easy-tomeasure index of children's motivation for, and engagement in, their school work (e.g., Toppino et al, 1991).…”
Section: The Role Of Recess In Cognitive Performance: Proximal Measuresmentioning
confidence: 99%
“…The interventions that were included in this category (see Table 1) focused on the application of behavior modification techniques (Fabiano & Pelham, 2003;Northup et al, 1999;Van Lier, Muthen, Van der Sar, & Crijnen, 2004), cognitive-behavioral techniques (Ardoin & Martens, 2004;DuPaul & Hoff, 1998;Mathes & Bender, 1997), or environmental changes that involve modifications in the usual classroom dynamics (Powell & Nelson, 1997;Ridgway, Northup, Pellegrin, LaRue, & Hightsoe, 2003). Decrease disruptive behavior and increase "on-task" behavior.…”
Section: Simple Interventionsmentioning
confidence: 99%
“…In a thesis on children with attention deficit disorder and hyperactivity disorder, Yılmaz investigated another dimension of the topic and reached the conclusion that the children with attention deficit disorder and hyperactivity disorder socialized in a positive way during free time activities [61]. In a study on ADHD students, Ridgway et al [62] compared the days when children had recess and when they did not. They concluded that the children showed more inappropriate behavior in the days when they did not have recess.…”
Section: Discussionmentioning
confidence: 99%